2007
DOI: 10.1080/09593980701593755
|View full text |Cite
|
Sign up to set email alerts
|

Are elderly pedestrians allowed enough time at pedestrian crossings in Cape Town, South Africa?

Abstract: A descriptive, cross-sectional analytical study was conducted to determine whether the recommended walking speed of 1.2 ms(-1) would allow elderly pedestrians to safely clear pedestrian crossings in Cape Town, South Africa. Male and female volunteers (n = 47), aged 65-93 years and resident in four homes for older persons, were recruited. Pedestrian clearance intervals at 40 traffic lights within 5-km radius of the selected homes were measured. The mean walking speed required at these traffic lights was 0.86 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 13 publications
4
27
0
1
Order By: Relevance
“…Asher et al (2012) found that 84% of older men and 93% of older women were not able to cross streets safely as their walking speed was not fast enough to cross the road in time. A similar result was found in both Amosun, Burgess, Groeneveldt and Hodgson [48] and Loo and Tsui [75]. The design of pedestrian/cycling environments was also identified as a barrier for walking and cycling.…”
Section: Walking and Cyclingsupporting
confidence: 72%
See 1 more Smart Citation
“…Asher et al (2012) found that 84% of older men and 93% of older women were not able to cross streets safely as their walking speed was not fast enough to cross the road in time. A similar result was found in both Amosun, Burgess, Groeneveldt and Hodgson [48] and Loo and Tsui [75]. The design of pedestrian/cycling environments was also identified as a barrier for walking and cycling.…”
Section: Walking and Cyclingsupporting
confidence: 72%
“…The former produces a dispersion of services and activities beyond a reasonable walking and cycling distance [2], the latter a divisive effect on residential areas [118]. Crossing the road in later life is particularly affected by community severance and road traffic issues, due to traffic volumes, speed, noise and pollutant emissions [48,55,62,77,79,87]. Asher et al (2012) found that 84% of older men and 93% of older women were not able to cross streets safely as their walking speed was not fast enough to cross the road in time.…”
Section: Walking and Cyclingmentioning
confidence: 99%
“…The evidence that does exist indicates that older people, whether walking or using public transport, have a significant exposure to accidents and injury [47]. Even crossing roads in busy urban environments in LAMICs may (rightly) induce feelings of anxiety and fear, with a consequent impact on quality of life [48]. Although data limitations mean that studies have tended to be small-scale, they nevertheless raise important issues.…”
Section: Ageing Health and Mobilitymentioning
confidence: 99%
“…Overall, the time allowed by traffic lights for pedestrians to cross the street has been shown to be insufficient for most older people (Amosun et al, 2007;Asher et al, 2012;Hoxie and Rubenstein, 1994). The need to hurry is frequent in older adults and is associated with anxiety, despite the presence of traffic lights (Amosun et al, 2007;Hoxie and Rubenstein, 1994) and this may provoke reluctance to cross. Traffic lights should therefore be designed to offer older adults enough time to cross safely and calmly.…”
Section: Ergonomic Design Of Road Environments and Carsmentioning
confidence: 99%